Analisis Perlindungan Hukum bagi Investor Pasar Modal melalui Kebijakan Disorgement Fund - RETNO CATUR KUSUMA DEWI; MOHAMMAD CHOIRUL ANAM (Universitas Merdeka Madiun, 2023)
This research aims to analyze the disorgement mechanism through the RPOJK regulation so that it can be applied to capital market problems and alternative legal settlements. The research method used in this research is a normative juridical approach with an invitational approach. Based on research results such as the disgorgement arrangement by the OJK as a form of funds through civil sanctions such as compensation, it can be a form of administration as a form of investor legal protection because disgorgement embodies such as efficient, equal funds and can be preventive measures